1988
DOI: 10.1016/0013-4686(88)80223-8
|View full text |Cite
|
Sign up to set email alerts
|

Galvanostatic anodization of titanium—I. Structures and compositions of the anodic films

Abstract: The galvanostatic anodization of commercially pure titanium is studied with current densities lower than 500 A m " Mn 1 M sulphuric acid between 25 and 75°C. Two types of electrochemical behaviour are observed; the first type is characterized by a maximutn value of the cell voltage and the second one by a continuous increase of the anode to cathode (which is platinum) potential différence. Thèse différent behaviours may be related to différent structures of the anodic films (as observed by SEM and TEM) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 22 publications
6
87
0
3
Order By: Relevance
“…to allow them to completely selforganize), this variation shows that the grain structure slightly influences also the nanotube diameter. It is known from literature, that the thickness of anodic TiO2 films is directly proportional to the applied voltage [1][2][3][4][5][6]. The same rule also applies for the nanotube diameter vs. voltage used for the nanotube growth [9,22,23].…”
Section: Resultsmentioning
confidence: 82%
“…to allow them to completely selforganize), this variation shows that the grain structure slightly influences also the nanotube diameter. It is known from literature, that the thickness of anodic TiO2 films is directly proportional to the applied voltage [1][2][3][4][5][6]. The same rule also applies for the nanotube diameter vs. voltage used for the nanotube growth [9,22,23].…”
Section: Resultsmentioning
confidence: 82%
“…(The explanation for the electrochemical processes involved in anodization can be found in several works (48)(49)(50)(79)(80)(81)(82)(83)(84).) The anodic oxide film growth is a two-stage process that results in either a thin or thick titanium oxide film: up to 160 V of applied voltage drop in the electrochemical cell, a linear growth in the nanometric range of the TiO 2 film is achieved (50); when anodization is carried out at higher voltages, an increased gas evolution and often sparking are obtained, resulting in titanium oxide films up to tenth µm thickness.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Oxygen generated at the anodic surface then combines with the titanium to form titanium oxide. As the oxide thickens it increasingly acts as an electrical insulator between the electrolyte and the anode until the point where there are too few OH-ions available to support further growth, The oxide thickness at which this occurs is primarily a function of the applied voltage but there have been a large number of studies on the properties of the oxide films [13][14][15][16], which have showed that the composition and microstructure of the anodic oxides are also strongly dependent on other factors such as electrolyte concentration, temperature and anodic surface conditions [17]. This means there are a lot of variables to control for an artist.…”
Section: Introductionmentioning
confidence: 99%